2022
DOI: 10.3390/catal12101174
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Methanol Steam Reforming on Ni2P Catalyst

Abstract: Methanol steam reforming (MSR) is a promising technology for on-board hydrogen production in fuel cell applications. Although traditional Cu-based catalysts demonstrate high catalytic activity and selectivity towards CO2 relative to CO, which is produced via methanol decomposition, they suffer from poor thermal stability and rapid coke formation. Nickel phosphides have been widely investigated in recent years for many different catalytic reactions owing to their remarkable activity and selectivity, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Next, we present a thorough analysis of the reaction pathways shown in Scheme 1 on Ni and Ni 12 P 5 . We compare these results with our prior work on Ni 2 P to elucidate the effects of the P:Ni atomic ratio on selectivity and reactivity [ 32 ]. The reaction network, as illustrated in Scheme 1 , serves as the basis for our investigation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Next, we present a thorough analysis of the reaction pathways shown in Scheme 1 on Ni and Ni 12 P 5 . We compare these results with our prior work on Ni 2 P to elucidate the effects of the P:Ni atomic ratio on selectivity and reactivity [ 32 ]. The reaction network, as illustrated in Scheme 1 , serves as the basis for our investigation.…”
Section: Resultsmentioning
confidence: 97%
“…The primary goal of catalyst performance enhancement for MSR is to increase the rate of hydrogen production and improve CO 2 selectivity while using a thermally stable material. Transition metal phosphides (TMPs) have emerged recently as a highly versatile class of catalysts which can be used for a wide range of applications due to their unique selectivity and resistance to coke formation [ 29 , 30 , 31 , 32 , 33 ]. Among those TMPs, nickel phosphides (Ni x P y ) have been previously examined for C–O bond cleavage in biomass-derived molecules [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, nickel phosphide catalysts exhibit enhanced selectivity towards breaking tertiary 3 C-O bonds in oxygenate compounds, in contrast to pure nickel catalysts where secondary 2 C-O bond cleavage is favored [24]. Furthermore, phosphorus incorporation improved activity and selectivity in other reactions, such as methanol steam reforming and methane activation [25,26]. These findings suggest that phosphorus modification could potentially fine-tune catalytic properties for specific target reactions [27].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we explore the catalytic performance of the Ni 2 P catalyst doped with Fe and Ru for ammonia synthesis using DFT. We have previously shown that incorporating phosphorus atoms in nickel phosphide catalysts can alter the catalytic behavior of Ni atoms, leading to improved selectivity for various catalytic reactions [19][20][21]. The P atoms introduce weak binding surface sites that disrupt the metal ensembles.…”
Section: Introductionmentioning
confidence: 99%